KONSEP DASAR ASESMEN DAN EVALUASI DALAM PAI - Moh Maimun; Moh Sahlan; M Ilham Fikron; Achmad Muzammil (PT. Sulthan Journal Publisher, 2026)
Assessment and evaluation are essential components of the Islamic Religious Education (PAI) learning process, serving to determine the level of student competency achievement and the effectiveness of the learning process. This study aims to describe the basic concepts of assessment and evaluation in Islamic Religious Education (PAI), including their definitions, differences, functions, and the principles educators must consider in their implementation. The method used was library research, reviewing various relevant literature sources, such as books, journals, and educational documents. The results indicate that assessment is the process of continuously collecting and processing information regarding student learning outcomes, while evaluation is the process of making decisions based on the data obtained from the assessment. In the context of PAI, assessment and evaluation focus not only on cognitive aspects but also include affective and psychomotor aspects that reflect the mastery of Islamic values ​​in everyday life. Therefore, appropriate implementation of assessment and evaluation can help improve the quality of PAI learning and support the optimal achievement of Islamic education goals.